Dementia with Lewy Bodies : Clinical and Biological Aspects - Kosaka, Kenji (Springer Japan : Imprint: Springer, 2017)
This book describes biological and clinical aspects of dementia with Lewy bodies (DLB), one of the most common types of progressive dementia, although in most cases the cause is unknown. The editor has made a major contribution to the understanding of the disease since he first reported DLB in 1976. Written by renowned experts in the field, the book discusses not only diagnostic criteria and clinical symptoms of DLB but also various imaging modalities and biological markers such as alpha-synuclein, which are useful for diagnosis of DLB. Dementia with Lewy Bodies is aimed at psychiatrists, neurologists, and researchers who are interested in DLB.
Keywords: Medicine.; Neuroradiology.; Neurology.; Psychiatry.; elektronické knihy; electronic books